(untitled) (Research, Society and Development, 2020)
Objective: To determine whether the use of licit and illicit drugs, the use of antibiotics, medicinal plants and drugs acting on the central nervous system are risk factors for structural fetal changes. Methods: Case-control study, conducted between July 2017 and October 2018, in a public fetal medicine hospital. The case population consisted of 202 pregnant women of fetuses with structural malformations and the control population of 80 pregnant women. A questionnaire was applied before the ultrasound evaluation, in order to analyze the clinical and epidemiological data. Results: The ingestion of amoxicillin (OR: 0.35), spiramycin (OR: 0.05), passionflower (OR: 0.09) and sertraline (OR: 0.18) showed a negative association, with indicative of protection against malformations fetal structures. There was an inappropriate use of folic acid and high consumption of medications. Conclusion: The use of alcohol, cigarettes, illicit drugs, antibiotics, medicinal plants and drugs that act on the central nervous system did not define an increased risk for structural fetal malformations. However, it demonstrates the lack of awareness about the importance of family planning and the dangers of using drugs during pregnancy.